Government export support program in Egypt: Challenges and influencing factors - Alhelewa, Ahmed Kamal (AUC Knowledge Fountain, 2020)
The purpose of this research is to examine the challenges and influencing factors of the Government Export Support Program (ESP) in Egypt. The program was initiated in 2002 with the aim of upgrading the value added of Egyptian exporters and strengthening their international market share. The research identifies twelve challenges categorized into two groups: 1) program design issues (service-based not result-based program, absence of strong monitoring and evaluation systems, a lack of a sustainability strategy, underrepresentation of private sector in the board of directors of the Export Development Fund, restricted support and rigid budget distribution, inappropriate response to different needs of exporters, limited support to potential exporters, and putting SMEs at a disadvantage for obtaining the support); and 2) program implementation (continuous change of implementing agencies and regulations of participation in international trade fairs, bureaucracy and long procedures, lack of financial resources of implementing agencies, and low performance of government employees). The analysis also identifies eight influencing factors related to firm capabilities (unavailability of information about international markets, difficulty in meeting competitors’ prices, suffering in finding new export opportunities and reliable customers, lack of financial resources, and obstacle of compliance with product quality and standards); and to the export business environment (low efficiency of trading across boarder, absence of industrial and trade policy, and governance challenges of public institutions). Several recommendations are derived to inform policy makers about proposed actions in order to improve the program performance.